Can fungal endophytes suppress Trialeurodes vaporariorum and the transmission of tomato infectious chlorosis and chlorosis viruses in field conditions? - Paweer, Marial Makur Zechariah; Namikoye, Everlyne Samita; Nchore, Shem Bonuke; Akutse, Komivi Senyo (Frontiers in Cellular and Infection Microbiology, 2025)
Field trials were conducted for two seasons in two experimental sites (Mwea in Kirinyaga and Ngoliba in Kiambu counties of Kenya) to assess the efficacy of fungal endophytes Hypocrea lixii F3ST1 and Trichoderma asperellum M2RT4 in the control of Trialeurodes vaporariorum vector of tomato infectious chlorosis virus (TICV) and tomato chlorosis virus (ToCV) through seeds inoculation. TICV and ToCV’s disease incidence, severity and the yield were also evaluated. All the fungal endophytes successfully colonized all the tomato plant parts, but the highest root colonization was observed in H. lixii F3ST1 compared to the T. asperellum M2RT4 in both seasons. The number of nymphs was significantly lower in the endophytically colonized tomato plants than the control treatments in all the seasons and at both sites. However, the lowest number of nymphs was recorded in H. lixii F3ST1 compared to T. asperellum M2RT4. On the other hand, the TICV and ToCV disease incidence and severity rates were lower in endophytically colonized tomato crops compared to the control plots. This could be attributed to the reduction in the virus replication and lower feeding ability of T. vaporariorum that was characterized by less excretion of honeydew causing sooty mold. However, no significant difference was observed in ToCV disease severity rates among the treatments and across the seasons. The yield was significantly higher in endophyte plots than the control treatments in both sites and across the two seasons. This study demonstrates that H. lixii F3ST1 and T. asperellum M2RT4 endophytically colonized tomato plants and conferred systemic resistance against T. vaporariorum vector, and significantly reduced the transmission of TICV and ToCV, contributing to high reduction of both diseases’ incidence and severity in the field. However, further studies are warranted to confirm these results at large scale trials.